Ketamine: stimulating antidepressant treatment?. Issue 3 (May 2016) - Malhi, Gin S.; Byrow, Yulisha; Cassidy, Frederick; Cipriani, Andrea; Demyttenaere, Koen; Frye, Mark A.; Gitlin, Michael; Kennedy, Sidney H.; Ketter, Terence A.; Lam, Raymond W.; McShane, Rupert; Mitchell, Alex J.; et al.
Summary: The appeal of ketamine – in promptly ameliorating depressive symptoms even in those with non-response – has led to a dramatic increase in its off-label use. Initial promising results await robust corroboration and key questions remain, particularly concerning its long-term administration. It is, therefore, timely to review the opinions of mood disorder experts worldwide pertaining to ketamine's potential as an option for treating depression and provide a synthesis of perspectives – derived from evidence and clinical experience – and to consider strategies for future investigations.